Mitochondrial metabolism regulates macrophage biology - Wang, Yafang (J Biol Chem, 2021)
Mitochondria are critical for regulation of the activation, differentiation, and survival of macrophages and other immune cells. In response to various extracellular signals, such as microbial or viral infection, changes to mitochondrial metabolism and physiology could underlie the corresponding state of macrophage activation. These changes include alterations of oxidative metabolism, mitochondrial membrane potential, and tricarboxylic acid (TCA) cycling, as well as the release of mitochondrial reactive oxygen species (mtROS) and mitochondrial DNA (mtDNA) and transformation of the mitochondrial ultrastructure. Here, we provide an updated review of how changes in mitochondrial metabolism and various metabolites such as fumarate, succinate, and itaconate coordinate to guide macrophage activation to distinct cellular states, thus clarifying the vital link between mitochondria metabolism and immunity. We also discuss how in disease settings, mitochondrial dysfunction and oxidative stress contribute to dysregulation of the inflammatory response. Therefore, mitochondria are a vital source of dynamic signals that regulate macrophage biology to fine-tune immune responses.